Pengaruh Pembiayaan Musyarakah Dan Pembiayaan Murabahah Terhadap Dana Pihak Ketiga (DPK) di Bank Pembiayaan Rakyat Syariah (BPRS) Indonesia Tahun 2017-2019 - Yunanda, Putri (JYRS: Journal of Youth Research and Studies, 2021)
The purpose of this study is to see the effect of musharaka financing and murabahah financing on Third Party Funds in Indonesian Sharia People's Financing Bank 2017-2019 simultaneously and partially. This research uses quantitative research, with associative methods and using secondary data sources. Data teaching techniques are documentation and literature study. The results of this study indicate that simultaneous musyarakah financing and murabahah financing have a significant effect on Third Party Funds in Indonesian Bank Pembiayaan Rakyat Syariah (BPRS) for 2017-2019, with a value of 8.887047 and a significant value of 0, 000817, with a significant value of 0.000817 < 0.05. Whereas partially musyarakah financing has a positive and significant effect on Third Party Funds (DPK) in Bank Pembiayaan Rakyat Syariah (BPRS) for 2017-2019, with a t-statistic value of 3.547399, and murabahah financing has a positive and significant effect on Third Party Funds at the Bank Pembiayaan Rakyat Syariah (BPRS) Indonesia for 2017-2019, with a t-statistic value of 1.342430. For the development of science, further research is expected to add other variables but which have not been included in research related to Third Party Funds. These variables include mudharabah financing, ijarah, and other variables related to Third Party Funds.